La disortografía en el proceso de enseñanza y aprendizaje. - Barraquel Chifla, Mariela Aracelly (2018)
The project about dysorthography in the teaching-learning process was developed considering the writing difficulties in the fourth-year students of Basic Education. Students have trouble recognizing letters and therefore their writing has recurrent spelling mistakes that make them difficult to understand students’ ideas and thoughts. It is vital to mention that writing with bad spelling can have a direct impact on their grades and school performance. For this reason, the objective of this research is to analyze the factors that affect dysorthography in the teaching-learning process in the language and literature area. The methodology applied was the qualitative approach. It also has a bibliographic-documental and field design that allow to clarify the knowledge about the factors in dysorthography. The beneficiaries of this research were the students, teachers and parents of the fourth year of Basic Education at Huayna Capac Educative Unit. The results allowed to identify two factors that affect dysorthography in students. The first factor is the cultural dysorthography in which the students have difficulties for the internalization and application of the orthographic rules, mainly in the correct use of the letters b, v, s, c, z, d, p, q, m, n. The second factor is teachers´ lack of knowledge on the use of strategies to teach, identify and intervene in dysorthography problems in students. It is concluded that the little knowledge in teaching orthography affects in the graphemes and phonemes confusion that leads to the problem of dysorthography. It is recommended that teachers apply strategies to help improve students’ orthography and thus they can improve their grades and their school performance.